CONTROLE QUÃMICO DA MANCHA PARDA E CRESTAMENTO FOLIAR DA SOJA (Glycine Max (L.) Merrill) - Lopes, Maria Elizabete Barretto M.; Gunnewieck, Rennee A. Klein; Barros, Benedito de Camargo; Sinigaglia, Celso (REVISTA DE AGRICULTURA, 2015)
CONTROLE QUÃMICO DA MANCHA PARDA E CRESTAMENTO FOLIAR DA SOJA (Glycine Max (L.) Merrill)